Concordance of Human Papillomavirus Type 16 and 18 in Cervical and Oral Specimen of Cervical Cancer Patients - Akbar, Willy; Rauf, Syahrul; S. Riu, Deviana; T. Chalid, St. Maisuri (Indonesian Journal of Obstetrics and Gynecology, 2019)
Abstract Objective : To determine the conformity of HPV type 16 and 18 in cervical and oral/buccal specimens from cervical cancer patients. Methods :A cross-sectional study was conducted in March - September 2016 at several hospitals in Makassar. HPV 16 and 18 genotyping in cervical and oral fluid of 77 patients with cervical cancer performed with PCR method. Results : The prevalence of HPV type 18 infection both in the cervical and the oral fluid was higher than HPV type 16 [9(47.4%) vs 5(26.3%)]. The aggreement of HPV type 18 infection (r=0.328;p=0.000) in the cervical-oral sites was higher than HPV type 16 (r=0.194;p=0.042). Conclusion : HPV type 16 and 18 could infect both cervix and oral cavity although type-specific concordance is low. Keywords :Human papillomavirus,servix, oral cavity   Abstrak Tujuan: Mengetahui tingkat kesesuaian hasil pemeriksaan HPV tipe 16 dan 18 antara spesimen serviks dan oral/buccal pada penderita kanker serviks. Metode: Penelitian cross sectional ini dilakukan pada Maret – September 2016 pada beberapa rumah sakit di Makassar. Pemeriksaan HPV 16 dan 18 pada cairan serviks dan oral dari 77 orang penderita kanker serviks menggunakan teknik PCR. Hasil: Prevalensi infeksi bersama pada serviks dan oral HPV tipe 18 lebih tinggi dibandingkan HPV tipe 16 [9(47,4%) vs 5(26,3%)]. Tingkat kesesuaian antara HPV tipe 18 (r=0,328;p=0,000) pada serviks dan oral lebih tinggi dibandingkan tipe 16 (r=0,194;p=0,042). Kesimpulan: HPV tipe 16 dan 18 dapat menginfeksi serviks dan oral meskipun tingkat kesesuaian kedua tipe ini lemah. Kata kunci : Human papillomavirus, serviks, kavum oral